Death Receptor Interactions With the Mitochondrial Cell Death Pathway During Immune Cell-, Drug- and Toxin-Induced Liver Damage - Spinnenhirn, Valentina; Demgenski, Janine; Brunner, Thomas (Frontiers in Cell and Developmental Biology, 2019)
Due to its extensive vascularization and physiological function as a filter and storage organ, the liver is constantly exposed to infectious and tumorigenic threat, as well as damaging actions of xenobiotics. Detoxification reactions are essential for the excretion of harmful substances, but harbor also the risk of “side effects” leading to dangerous metabolites of otherwise harmless substances, a well known effect during paracetamol overdose. These drugs can have detrimental effects, which often involves the induction of sterile inflammation and activation of the immune system. Therefore, the role of certain immune cells and their effector molecules in the regulation of drug-induced liver damage are of special interest. Hepatocytes are type II cells, and death receptor-induced cell death requires amplification via the mitochondrial pathway. However, this important role of the mitochondria and associated cell death-regulating signaling complexes appears to be not restricted to death receptor signaling, but to extend to drug-induced activation of mitochondrial cell death pathways. We here discuss the role of members of the Tumor Necrosis Factor family, with a focus on TRAIL, and their interactions with the Bcl-2 family in the crosstalk between the extrinsic and intrinsic cell death pathway during xenobiotic-induced liver damage.